Carpe Diem: Southern Connecticut State University 2005 Championship Season - Shea, Timothy K. (2005)
Keywords: Baseball; Baseball; Connecticut; Connecticut; College sports; Southern Connecticut State University; dept.ath; faculty_collection

The Psychology of Athletic Coaching - Moore, J. W. (Burgess Pub. Co, 1970)
Keywords: Coaching (Athletics); dept.ath; faculty_collection

Football Techniques Illustrated. - Moore, J. W. (Ronald Press Co, 1962)
Keywords: Football; dept.ath; faculty_collection

Proficiency in the Performance of Selected Physical Education Skills and Success in Teaching Those Skills - Metrelis, Dora M. (Thesis D.P.E.--Springfield College., 1971)
Keywords: Physical education for women; Study and teaching; Physical education teachers; Study and teaching; Sports for women; dept.ath; dept.hms; faculty_collection

The Effects of Low-Dose Creatine Supplementation Versus Creatine Loading in Collegiate Football Players - Wilder, N.; Deivert, R.G.; Hagerman, F.; Gilders, R. (Journal of Athletic Training, 2001)
Objective: To compare the effects of low doses of creatine and creatine loading on strength, urinary creatinine concentration, and percentage of body fat. Design and Setting: Division IA collegiate football players took creatine monohydrate for 10 weeks during a sport-specific, periodized, off-season strength and conditioning program. One-repetition maximum (1-RM) squat, urinary creatinine concentrations, and percentage of body fat were analyzed. Subjects: Twenty-five highly trained, Division IA collegiate football players with at least 1 year of college playing experience. Measurements: We tested strength with a 1-RM squat exercise before, during, and after creatine supplementation. Percentage of body fat was measured by hydrostatic weighing before and after supplementation. Urinary creatinine concentration was measured via light spectrophotometer at 0, 1, 3, 7, 14, 21, 28, 35, 42, 48, 56, and 63 days. An analysis of variance with repeated measures was computed to compare means for all variables. Results: Creatine supplementation had no significant group, time, or interaction effects on strength, urinary creatinine concentration, or percentage of body fat. However, significant time effects were found for 1-RM squat and fat-free mass in all groups. Conclusions: Our data suggest that creatine monohydrate in any amount does not have any beneficial ergogenic effects in highly trained collegiate football players. However, a proper resistance training stimulus for 10 weeks can increase strength and fat-free mass in highly trained athletes.
Keywords: Creatine phosphate; Ergogenic aids; Resistance training; dept.ath; ⛔ No DOI found

Changes During the 110 Years of the World Artistic Gymnastics Championships - Grossfeld, A. (Science of Gymnastics Journal, 2014)
This article presents changes, along with historical perspectives, in the World Gymnastics Championships during the last 110 years - 1903 to 2013. Changes include: the events contested, team and individual achievements and dominance, debut of skills, difficulty expansion, judges, scoring, competition format, Finals qualification system, expansion of FIG affiliation, frequency cycle of the WC, number of teams and gymnasts per competition, age requirement of gymnasts, team size, venues, apparatus, devices for learning, education and certification courses, disseminating information, and expanded media coverage.
Keywords: Gymnasts; History; Judges; Rules; dept.ath; ⛔ No DOI found